Food preservation techniques - Zeuthen, P.; Bøgh-Sørensen, Leif (CRC Press ; Woodhead, 2003)
Extending the shelf-life of foods whilst maintaining safety and quality is a critical issue for the food industry. As a result there have been major developments in food preservation techniques, which are summarised in this authoritative collection. The first part of the book examines the key issue of maintaining safety as preservation methods become more varied and complex. The rest of the book looks both at individual technologies and how they are combined to achieve the right balance of safety, quality and shelf-life for particular products.
Keywords: Food -- Preservation.; Food -- Safety measures.; elektronické knihy; electronic books